A Conceptual Scheme to Support the Identification of Consolidation Requirements in Open Design - da Silva Junior, Deógenes P.; Pereira, Roberto (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Consolidation is an important process to transform design objects from various sources into a coherent whole. In Open Design, the diversity of activities, design objects and participants involved implies in a rich context for Consolidation practice, but a challenging one in terms of features to support it. This paper presents a Conceptual Scheme created to help understanding and identifying Consolidation requirements for Open Design settings. The Scheme was evaluated with eight Open Design professionals in an exploratory case study, resulting in 49 requirements for an Open Design platform under development. In a Focus Group, professionals discussed the Scheme usage, its positive points and opportunities for improvements. Results suggest the Scheme was relevant for the professionals to understand Consolidation as a defined, comprehensive and applicable process in an Open Design context, and was useful to guide them from understanding Consolidation to identifying requirements to support it in a technical system.